Developmental performance in small for gestational age children with and without catch-up growth - Hesti Lestari; Suryani As’ad; Irawan Yusuf; Adrian Umboh; Andi Dwi Bahagia Febriani (Paediatrica Indonesiana, 2015)
Background Infants born small for gestational age (SGA) have an increased risk of developmental delay. The influence of catch-up growth on developmental function remains unknown.Objective To compare the development of SGA children with and without catch-up growth.Methods We conducted a cross-sectional study in Manado from March to July 2013. Subjects were children aged 2-3 years, that born SGA from March 2010 to June 2011 in Prof. Dr. R.D. Kandou Hospital. Catch-up growth was defined as height-for-age more than -2SD on the 2006 WHO growth chart, and subjects were classified into the with and without catch-up growth groups. Developmental status was assessed using the Ages and Stages Questionnaire (ASQ) 3rd edition, through interviews with parents. We compared the developmental status between the with and without catch-up growth groups used Mann-Whitney test with a significance level of P < 0.05.Results Of the 112 SGA children, 66 (58.9%) had catch-up growth and 46 (41.1%) did not. The SGA children with catch up growth had significant better development performances of gross motor, fine motor, and problem solving. The mean ASQ centiles of the with and without catch-up groups were 55.15 (SD 7.843) [95%CI 53.52 to 57.08] and 48.80 (SD 11.264) [95%CI 45.46 to 52.15] in gross motor, respectively; 42.5 (SD 13.163) [95%CI 39.26 to 45.74] and 32.93 (SD 14.475) [95%CI 28.64 to 37.23] in fine motor, respectively; 46.74 (SD 13.112) [95%CI 43.52 to 49.97] and 40.98 (SD 11.480) [95%CI 37.57 to 44.39] in problem solving, respectively.Conclusion Small for gestational age children with catch-up growth have significantly better gross motor, fine motor, and problem-solving performance than those without catch-up growth.